Exosomes: vesicular carriers for intercellular communication in neurodegenerative disorders - Schneider, Anja (Springer-Verlag, 2012)
The intercellular transfer of misfolded proteins has received increasing attention in various neurodegenerative diseases characterized by the aggregation of specific proteins, as observed in Alzheimer’s, Parkinson’s and Huntington’s disease. One hypothesis holds that intercellular dissemination of these aggregates within the central nervous system results in the seeded assembly of the cognate soluble protein in target cells, similar to that proposed for transmissible prion diseases. The molecular mechanisms underlying the intercellular transfer of these proteinaceous aggregates are poorly understood. Various transfer modes of misfolded proteins including continuous cell-cell contacts such as nanotubes, unconventional secretion or microvesicle/exosome-associated dissemination have been suggested. Cells can release proteins, lipids and nucleic acids by vesicular exocytosis pathways destined for horizontal transfer. Encapsulation into microvesicular/exosomal vehicles not only protects these molecules from degradation and dilution in the extracellular space but also facilitates delivery over large distances, e.g. within the blood flow or interstitial fluid. Specific surface ligands might allow the highly efficient and targeted uptake of these vesicles by recipient cells. In this review, we focus on the cell biology and function of neuronal microvesicles/exosomes and discuss the evidence for pathogenic intercellular protein transfer mediated by vesicular carriers.